2022
DOI: 10.1002/cm.21719
|View full text |Cite
|
Sign up to set email alerts
|

Espin overexpression causes stereocilia defects and provides an anti‐capping effect on actin polymerization

Abstract: Stereocilia are actin-based projections of hair cells that are arranged in a step like array, in rows of increasing height, and that constitute the mechanosensory organelle used for the senses of hearing and balance. In order to function properly, stereocilia must attain precise sizes in different hair cell types and must coordinately form distinct rows with varying lengths. Espins are actin-bundling proteins that have a wellcharacterized role in stereocilia formation; loss of function mutations in Espin resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(74 reference statements)
0
1
1
Order By: Relevance
“…In addition, we found that in vivo Espin overexpression did not significantly increase the length of stereocilia in neonatal HCs. However, a previous study found that the length of stereocilia increased and became thicker at P60 after Espin overexpression, 20 which was inconsistent with our results. We increased the expression of Espin in regenerated HCs and in situ HCs with persistent overexpression of Atoh1, rather than HCs unaffected by Atoh1, where the expression of Atoh1 causes changes in HCs, so the stereocilia changes caused by Espin overexpression are inconsistent with the previous research.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that in vivo Espin overexpression did not significantly increase the length of stereocilia in neonatal HCs. However, a previous study found that the length of stereocilia increased and became thicker at P60 after Espin overexpression, 20 which was inconsistent with our results. We increased the expression of Espin in regenerated HCs and in situ HCs with persistent overexpression of Atoh1, rather than HCs unaffected by Atoh1, where the expression of Atoh1 causes changes in HCs, so the stereocilia changes caused by Espin overexpression are inconsistent with the previous research.…”
Section: Discussioncontrasting
confidence: 99%
“…Until P60, it was found that the stereocilia of HCs became thicker and the length of different rows of stereocilia increased differently, but no hearing function was tested. 20 Furthermore, an in vitro study found that Espin overexpression in regenerated vestibular HCs induced by Notch inhibition led to an increase in hair-bundle-like structures, suggesting that Espin overexpression might be involved in the injury or regeneration of stereocilia. 21 However, only in vitro experiments were conducted, and the effect on stereocilia in IHCs and OHCs was not studied in this study.…”
Section: Introductionmentioning
confidence: 99%